Free Internet access as a human right / Merten Reglitz. - Reglitz, Merten (Cambridge University Press, 2024)
Merten Reglitz proposes a new human right that ensures Internet access for those who cannot afford it and protects that right from arbitrary interferences by those that would exploit it for harm. The first part of the book justifies the claim for this new right by showing how Internet access is vital for the enjoyment of human rights around the globe. In the second part, Reglitz specifies the content of this right, assessing today's standard threats to Internet access. He recommends a minimum international standard of connectivity and explains how states have misused the Internet. He documents how private companies already manipulate both internet access and content to maximise profit, and how lack of rights enforcement allows people to harm others online. The book establishes that a new human right to free internet access is essential to secure its role for the benefit and progress, not detriment, of humanity.